Neuromorphic deviations associated with transcriptomic expression and specific cell type in Alzheimer’s disease - Jinzhong Peng; Qin Tang; Yilu Li; Lin Liu; Bharat Bhusan Biswal; Pan Wang (Scientific Reports)
Abstract Alzheimer’s disease (AD) is known to be associated with cortical anatomical atrophy and neurodegeneration across various brain regions. However, the relationships between brain structural changes in AD and gene expression remain unclear. We perform the morphometric similarity network (MSN) analysis to reveal the consistent cortical structural differences in individuals with AD compared to controls, and investigate the associations between brain-wide gene expression and morphometric changes. Furthermore, we identify abnormally MSN-related genes linked to specific cell types as the major contributors to transcriptomic relationships. MSN-related structural changes are located in the lateral ventral prefrontal cortex, temporal pole and medial prefrontal lobe, which are highly associated with the AD’s cognitive decline. Analysis of gene expression shows the spatial correlations between AD-related genes and MSN differences. Examination of cell type-specific signature genes indicates that changes in microglia and neuronal transcriptional profiles largely contribute to AD-specific MSN differences. The study map the disease-specific structural alterations in AD down to the cellular level, offering a novel perspective on the linking surface-level changes to molecular mechanisms.